Selective Removal of Perfluorooctanoic Acid Using Molecularly Imprinted Polymer-Modified TiO2 Nanotube Arrays - Yunbo Wu; Yi Li; Aijun Tian; Kai Mao; Jian Liu (International Journal of Photoenergy)
Perfluorinated chemicals have attracted worldwide concern owing to their wide occurrence and resistance to most conventional treatment processes. In this work, a novel photocatalyst was fabricated by modifying TiO2 nanotube arrays with molecularly imprinted polymers. The molecularly imprinted polymer-modified TiO2 nanotubes (MIP-TiO2 NTs) were characterized and tested for the selective removal of perfluorooctanoic acid (PFOA) from water. The amount of PFOA adsorbed by the MIP-TiO2 NTs was as high as 0.8125 μg/cm2. PFOA decomposition and defluorination by the MIP-TiO2 NTs reached 84% and 30.2% after 8 h reaction, respectively. The Freundlich model and pseudo-first-order kinetics were used to describe the observed adsorption and decomposition of PFOA, respectively. Compared with TiO2 NTs and nonmolecularly imprinted polymer-modified TiO2 NTs, the MIP-TiO2 NTs exhibited not only a higher PFOA degradation rate but also enhanced selectivity for target chemicals. The MIP-TiO2 NTs could also selectively and rapidly remove PFOA from secondary effluent, exhibiting a decomposition of 81.1%, almost as high as that observed in pure water. Investigation of the effects of scavengers on the photocatalytic reaction indicated that photogenerated holes were the main oxidant for PFOA decomposition, and the PFOA degradation mechanism and pathway were proposed.